SOCIAL ROLE AND FUNCTIONS OF RELIQIONS CONSIOUSNESS IN THE HISTORY OF PHILOSOPHICAL THOUGHT - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to determining religions consciousness social role and its functions in the history of philosophy.